If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12z + 12y + 13z + -1y = 0 Reorder the terms: 12y + -1y + 12z + 13z = 0 Combine like terms: 12y + -1y = 11y 11y + 12z + 13z = 0 Combine like terms: 12z + 13z = 25z 11y + 25z = 0 Solving 11y + 25z = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-25z' to each side of the equation. 11y + 25z + -25z = 0 + -25z Combine like terms: 25z + -25z = 0 11y + 0 = 0 + -25z 11y = 0 + -25z Remove the zero: 11y = -25z Divide each side by '11'. y = -2.272727273z Simplifying y = -2.272727273z
| N+4n=30 | | 4+4n=-12+2 | | w/2-3(12)=53 | | 8cos^2(x)+4cos(x)-1=0 | | -3x+9=6 | | 16-x/5=x/3 | | 4x(3+x)=16+x | | 6x-5-2x=3y+7-4x | | 7.2a=13.53+2.81a | | y-12=3y-2 | | .12a-.08b=0 | | 5n/3-3/7=61/21 | | 20m+12n-5m+13n+65= | | 5/r-9=8/r+5 | | 4x-24=4x+60 | | 6w-14=4w+24 | | 7x-1=-85 | | 6w-14=4w | | 1/2(2x+54)=1/3(9x+27) | | w/2-3(6)=53 | | 6/7x-3=45 | | (4x+3)/9-(2x+1)/2=0 | | 35+0.10p=25+0.25p | | 0.023X+0.08=0.36X-5.266 | | 35p+0.10=25p+0.25 | | 13b+9-12c= | | 8=g/7 | | 180=2x+(x-8)+x | | -2/5r+2r=1/5r+14/3 | | (4x+3)/9 | | -3x^2-14x-15=0 | | 8x-4x+3x-9x= |